Seasonal changes in the testicular activity of the Iranian Mountain Viper, Montivipera albicornuta (Nilson & Andrén, 1985) (Reptilia: Viperidae). Issue 1 (2nd January 2016) - Safdarian, Parvaneh; Todehdehghanb, Fatemeh; Hojatia, Vida; Shiravi, Abdolhossein
Abstract : The Iranian Mountain Viper, Montivipera albicornuta, is a venomous snake endemic to Iran. We compared the seasonal cycle of testicular activity of 74 male specimens during a one-year period in two cold mountain climate habitats: Tarom (in Zanjan Province) and Bostanabad (in Eastern Azerbaijan Province) in northwestern Iran. The maximum testicular volume was observed in both habitats during autumn. The diameter of seminiferous tubules reached a maximum length in winter and a minimum in summer. The number of spermatids increased in autumn. Spermiogenesis occurred in spring and the maximum number of spermatozoa was reached then. In M. albicornuta in Iran, the testes were more active in autumn and spring, and spermatogenesis started in autumn and continued until mating in spring.